2002
DOI: 10.1046/j.1440-1754.2002.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 in the acute arthropathies and juvenile rheumatoid arthritis

Abstract: These data support the hypothesis that parvovirus B19 infection may be associated with the onset of juvenile rheumatoid arthritis in a proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 22 publications
0
19
0
3
Order By: Relevance
“…All children were followed over time to assess the progress of arthropathy to JIA: seropositive cases significantly drifted to progress to chronic arthritis and more likely to receive a final diagnosis of JIA than seronegative ones. These data suggested a role of parvovirus B19 for the development of JIA [37].…”
Section: The Potential Role Of Viruses In Juvenile Idiopathic Arthritismentioning
confidence: 75%
“…All children were followed over time to assess the progress of arthropathy to JIA: seropositive cases significantly drifted to progress to chronic arthritis and more likely to receive a final diagnosis of JIA than seronegative ones. These data suggested a role of parvovirus B19 for the development of JIA [37].…”
Section: The Potential Role Of Viruses In Juvenile Idiopathic Arthritismentioning
confidence: 75%
“…The virus may represent a trigger for both autoinflammation and autoimmunity. There are only few reports of parvovirus B19-induced autoimmunity, including rheumatoid arthritis, [16][17][18] systemic lupus erythematosus, 19,20 antiphospholipid syndrome, 21 systemic sclerosis and vasculitis. Lehmann et al 22 suggested that, in persistent parvovirus B19 infection, production of proinflammatory cytokines as a result of nonstructural protein 1 (nonstructural protein of parvovirus B19) may transactivate cellular promoter for the expansion of tumor necrosis factor-α and interleukin-6.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies link evidence of a previous Parvovirus B19 infection and parvo B19 viral persistence with the development of JIA and the presence of active disease. [20][21][22][23] Enteric and genitourinary tract organisms may play a triggering role in ERA, though none have been proven. Masi and Walsh 24 studied ERA patients with evidence of active synovitis.…”
Section: Environmental Triggers Of Jiamentioning
confidence: 99%